Using repurposed TVBox for maker, embedded systems and IoT activities - Araujo, Luiz Fernando Becher de; Oyamada, Marcio Seiji (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2025: Anais do XXII Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2025.15133, 2025)
The repurposing of illegal TVBox seized by the Brazilian Federal Revenue Service offers many opportunities for schools and universities. This type of initiative has a positive impact on the environment and the economy by avoiding the destruction of such devices, which generates waste and incurs costs. This work presents a methodology to convert these devices into prototyping board for maker, embedded systems, IoT, and robotics. This paper describes the process of identifying General Purpose Input/Output (GPIO) ports and presents practical examples of Python code for accessing them.